1997
DOI: 10.1177/0022022197281007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Language and Priming on the Relative Accessibility of the Private Self and the Collective Self

Abstract: An experiment addressed some limitations and implications of previous findings obtained by Trafimow, Triandis, and Goto suggesting that private and collective self-cognitions are stored in different cognitive locations. Consistent with expectations, priming the private self increased the retrieval of private self-cognitions, but priming the collective self increased the retrieval of collective self-cognitions. Further, retrieval of private and collective self-cognitions was clustered by type. The fact that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
149
2
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(172 citation statements)
references
References 16 publications
19
149
2
2
Order By: Relevance
“…Interdependent self-construals reflect self-definitions involving relationships to others; they emphasize belonging. People can experience both independent and interdependent self-construals as different self-schemas (Cross, Hardin, & Gercek-swing, 2011;Trafimow, Silverman, Fan, & Law, 1997;Trafimow, Triandis, & Goto, 1991). All people therefore have varying levels of independent/interdependent self-construals (Lu & Gilmour, 2007;Singelis, 1994), and the relative strength of each depends on personal social/cultural experiences and situations (Markus & Kitayama, 1991;Trafimow et al, 1991).…”
Section: Interaction Effect Of Self-construal and Work Characteristicsmentioning
confidence: 99%
“…Interdependent self-construals reflect self-definitions involving relationships to others; they emphasize belonging. People can experience both independent and interdependent self-construals as different self-schemas (Cross, Hardin, & Gercek-swing, 2011;Trafimow, Silverman, Fan, & Law, 1997;Trafimow, Triandis, & Goto, 1991). All people therefore have varying levels of independent/interdependent self-construals (Lu & Gilmour, 2007;Singelis, 1994), and the relative strength of each depends on personal social/cultural experiences and situations (Markus & Kitayama, 1991;Trafimow et al, 1991).…”
Section: Interaction Effect Of Self-construal and Work Characteristicsmentioning
confidence: 99%
“…This finding is inconsistent with previous research on cultural mindsets and language use among bilinguals. According to previous studies, cultural cues in social contexts and environment would prime bilingual individual's cultural mindset, which leads to distinctive response patterns in ways of thinking, self-concept, personality, and emotion expression (Benez-Martínez et al, 2002;Boucher & O'Dowd, 2011;Chen & Bond, 2010;Chen et al, 2014;Lee et al, 2010;Oyserman & Lee, 2008;Trafimow et al,1997).…”
Section: Description Of Language Cultural and Sexual Variablesmentioning
confidence: 99%
“…Previous research suggested that in general, high endorsement of heritage culture (enculturation) is associated with more conservative sexual values, narrower repertoire of sexual behaviors, less sexual satisfaction, and less frequency in sexual activities; whereas, high endorsement of U.S. mainstream culture (acculturation) is related with more open attitudes towards sex, increased pleasure and arousal from sexual activities, less sexual guilt, and more sexual communication (Brotto et al, 2005;Morton & Gorzalka, 2013;Woo & Brotto, 2008;Woo, Brotto, & Gorzalka, 2011), which potentially leads to higher relationship and sexual satisfaction. Lee, Oyserman, & Bond, 2010;Marian & Neisser, 2000;Matsumoto, Anguas-Wong, & Martinex, 2008;Oyserman & Lee, 2008;Trafimow, Silverman, Fan, & Law, 1997;Verkuyten & Pouliasi, 2006). Because language triggers a different cultural mindset that likely influences sexual attitudes and values, the communication skills and sexual knowledge learned in English in a mainstream American setting may not be readily transferrable for Chinese bilinguals in their interaction with partners.…”
Section: Introductionmentioning
confidence: 99%
“…One powerful cue that is capable of triggering frame switching is language (Trafimow, Silverman, Fan, & Law, 1997). In this regard, a language "is 'a veil' over the reality of the culture in which it is used, involving an agreement of its users about what there is to be seen and how it should be seen" (Kim, 1988, p. 89).…”
Section: Self-conscious Emotions and Culturementioning
confidence: 99%